Cross-sectional associations between meal timing patterns and diet quality indices in Iranian women - Azadeh Lesani; Mansooreh Sadat Mojani-Qomi (Scientific Reports)
Abstract Meal timing patterns (MTPs) are associated with energy and macronutrient intake, but their combined impact with food intake on overall diet quality remains underexplored. This cross-sectional study examined the relationship between MTPs and diet quality in a sample of 574 Iranian women aged 20–60 years from Tehran. Dietary intake was evaluated via three 24-hour dietary recalls, and demographic and anthropometric data were also collected. K-means cluster analysis on the basis of five dietary factors: morning and evening energy proportions, pre-sleep fasting, eating windows, and eating occasions were used. Diet quality was assessed via the Healthy Eating Index 2015 (HEI-2015), Carbohydrate Food Quality Score (CFQS-4), and Cholesterol-Saturated Fat Index (CSI). Three MTPs clusters were identified “pre-sleep fasting”, “long-frequent”, and “late-short”. The HEI-2015 scores were lower for the “long-frequent” (fully adjusted: β = -2.85, 95% CI: -4.85 to -0.87) and “late-short” (-2.11, -4.12 to -0.23) patterns than for the “pre-sleep fasting” cluster. Only the “late-short” pattern was consistently associated with reduced CFQS-4 scores across all the models (-0.19, -0.32 to -0.07). No associations were detected between MTPs and CSI. Morning energy intake was positively associated with the HEI-2015 score (0.21, 0.12 to 0.30), whereas evening energy intake was inversely associated with the CFQS-4 score (-0.003, -0.09 to -0.001). Additionally, “pre-sleep fasting” was related to decreased CSI (-0.003, -0.001 to -0.00003). These findings suggest that long-frequent and late-short MTPs are linked to lower diet quality. Longitudinal studies are needed to confirm these results and their implications for health.